2016
DOI: 10.1016/j.drugalcdep.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

The individual and combined effects of phenmetrazine and mgluR2/3 agonist LY379268 on the motivation to self-administer cocaine

Abstract: Background The US Food and Drug Administration has not approved a treatment for cocaine addiction, possibly due in part to the fact that repeated cocaine use results in dysregulation of multiple neurotransmitter systems, including glutamate and dopamine, and an emergence of increased negative affective states and heightening motivation to take cocaine despite negative consequences. We used a combination therapy approach to assess whether modulation of both glutamate and dopamine transmission would reduce the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…In rats, mGlu 2/3 activation reduces motivation to self-administer cocaine as determined by a reduced breakpoint under a progressive ratio reinforcement schedule (Hao et al, 2010; Karkhanis et al, 2016). Studies evaluating self-administration of many drugs of abuse in rats have demonstrated that mGlu 2/3 activation by LY379268 reduces intake of amphetamine (Kim et al, 2005), methamphetamine (Crawford et al, 2013), alcohol (Sidhpura et al, 2010), and nicotine (Liechti et al, 2007).…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…In rats, mGlu 2/3 activation reduces motivation to self-administer cocaine as determined by a reduced breakpoint under a progressive ratio reinforcement schedule (Hao et al, 2010; Karkhanis et al, 2016). Studies evaluating self-administration of many drugs of abuse in rats have demonstrated that mGlu 2/3 activation by LY379268 reduces intake of amphetamine (Kim et al, 2005), methamphetamine (Crawford et al, 2013), alcohol (Sidhpura et al, 2010), and nicotine (Liechti et al, 2007).…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…After a 12‐hr latency, each pump (208 μl fill volume) released 1.0 μl/hr, providing a 7‐day dosage of 3.0 mg kg −1 day −1 LY379268. This dose was chosen to represent the range of doses used in previous studies showing efficacy of LY379268 in reducing cocaine and methamphetamine self‐administration in (Baptista et al., 2004; Crawford et al., 2013; Hao et al., 2010; Karkhanis et al., 2016). Rats in the 14‐day treatment group underwent the implantation procedure twice consecutively to give 14 days of continuous drug exposure.…”
Section: Methodsmentioning
confidence: 99%
“…112116 Accordingly, systemic administration of mGluR2/3 agonists can attenuate cocaine and methamphetamine self-administration as well as reinstatement behaviors. 117121 Moreover, the glutamate carboxypeptidase II (GCPII) inhibitor 2-(phosphonomethyl)-pentanedioic acid (2-PMPA), which is an indirect mGluR2/3 agonist, attenuates cocaine place preference, 122 cocaine self-administration, and cocaine relapse. 123,124…”
Section: Neural Structures and Transmitter Systems Promoting Pharmacomentioning
confidence: 99%
“…Targeting presynaptic metabotropic glutamate 2 and 3 receptors (mGluR2/3s) also appears as a promising pharmacotherapeutic strategy to manage psychostimulant addiction (for review, see). Animal studies show enduring neuroadaptations in mGluR2/3 receptors following repeated psychostimulant exposure, which contributes to synaptic plasticity in glutamate and DA levels that drives drug-taking and drug-seeking behavior. Accordingly, systemic administration of mGluR2/3 agonists can attenuate cocaine and methamphetamine self-administration as well as reinstatement behaviors. Moreover, the glutamate carboxypeptidase II (GCPII) inhibitor 2-(phosphonomethyl)-pentanedioic acid (2-PMPA), which is an indirect mGluR2/3 agonist, attenuates cocaine place preference, cocaine self-administration, and cocaine relapse. , …”
Section: Neural Structures and Transmitter Systems Promoting Pharmaco...mentioning
confidence: 99%